2019
DOI: 10.14746/ssp.2016.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Media coverage of corruption: the role of inter-media agenda setting in the context of media reporting on scandals

Abstract: The study focuses on two Slovak corruption cases, both well-documented and of similar social relevance, of which one did not receive any cross-media coverage. Moreover, the case of large-scale bribery was rather under-hyped in comparison to other major corruption scandals occurring in the country. The case of cronyism formed a typical example of extremely poor inter-media coverage of highly unfair and politicised cronyism. Through these cases, especially in the one in which the media failed to stimulate the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This is not to say that all of the media reported on all other large-scale corruption cases. The media is clearly selective in its reports on corruption (Školkay, 2016;Školkay, Ištoková, 2016). Yet this extremely significant case was initially ignored by the entire media (save for one partial and minor exception), 3 even though it later became one of the most discussed corruption cases.…”
Section: Research Questions and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This is not to say that all of the media reported on all other large-scale corruption cases. The media is clearly selective in its reports on corruption (Školkay, 2016;Školkay, Ištoková, 2016). Yet this extremely significant case was initially ignored by the entire media (save for one partial and minor exception), 3 even though it later became one of the most discussed corruption cases.…”
Section: Research Questions and Methodologymentioning
confidence: 99%
“…This is another interesting dynamic of this case; the agenda-setting factor. It would be very useful to explore how many corruption stories failed to attract nation-wide coverage due to being published initially in media which were not agendasetting, especially when the inter-media agenda-setting function was rather low (see Školkay, Ištoková, 2016).…”
Section: The Gorilla Case In the Slovakian Mediamentioning
confidence: 99%
“…Be that as it may, at mezzo level, Sikorski's (2017) meta-review research, in particular, revealed that structurally, in relation to ownership structures, partisanship of a news organisation and the competitive context tend to influence news coverage about political scandals. In general, the media neglect most corruption, providing selectively too little, and not too much scandal coverage (Entman, 2012;Školkay & Ištoková, 2016). Finally, at micro level, the collaborative role can turn into collusion among politicians and the media or a journalist (Školkay, 2016b).…”
Section: The Media and Politics: A Short Normative Theory And Very Basic Empirical Findingsmentioning
confidence: 99%